2001
DOI: 10.1080/10573560152120994
|View full text |Cite
|
Sign up to set email alerts
|

Homework Communication Problems: Perspectives of Special and General Education Parents

Abstract: M adhavi J ayanthi Independent Research Consultant J anet N elson U niversity of S outhern M ississippi Edward A. Polloway Lynchburg CollegeThe practice of including students with disabilities in general education classes has spawned interest in academic interventions, such as homework , that allow these students to be successful . Previous studies have revealed a number of communication problems that can limit the effectiveness of homework as an intervention. The purpose of the present study is to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
9
0
3
Order By: Relevance
“…Researchers have noted that positive relationships between parents and schools have not been adequately forged (Lovitt and Cushing 1999;Turnbull and Turnbull 1997;Vaughn et al 1988). Various studies have found that communication between schools and parents is dissatisfying (Harniss et al 2001;Kohler 1999;Munk et al 2001) and centred on conflict (Spann, Kohler, and Soenksen 2003). Other findings indicate that even when meetings are attended, parents have little influence in actual decision-making (Able-Boone et al 1992;Goldstein et al 1980).…”
mentioning
confidence: 95%
“…Researchers have noted that positive relationships between parents and schools have not been adequately forged (Lovitt and Cushing 1999;Turnbull and Turnbull 1997;Vaughn et al 1988). Various studies have found that communication between schools and parents is dissatisfying (Harniss et al 2001;Kohler 1999;Munk et al 2001) and centred on conflict (Spann, Kohler, and Soenksen 2003). Other findings indicate that even when meetings are attended, parents have little influence in actual decision-making (Able-Boone et al 1992;Goldstein et al 1980).…”
mentioning
confidence: 95%
“…Research on communication in the elementary years focuses on issues of homework and parent-teacher conferences (Munk et al, 2001). Research on communication in the elementary years focuses on issues of homework and parent-teacher conferences (Munk et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They identified some major areas of concerns, including lack of initiation of communication; delayed, inconsistent, and infrequent communication; lack of responsiveness to communication; and problems with clarity and usefulness of communication. In addition to these shared concerns, parents reported as a problem not being able to contact teachers when they (i.e., parents) were available (Munk et al, 2001). Many parents wished to receive more communication about their child's attendance, good news about the child, and the content that the child was learning in school (Leitch & Tangri, 1988).…”
Section: Current Teacher Practices Of Home-school Communication Schomentioning
confidence: 99%